Nudges and norms: on the political economy of soft paternalism - Schnellenbach, Jan (European journal of political economy, 2012)
This paper discusses soft (or libertarian) paternalism, as proposed among others by Thaler and Sunstein (2008). It is argued that soft paternalism should not be understood as an efficiency-enhancing, but as a redistributive concept. The relationship between soft paternalism and social norms is discussed in detail. In particular, it is argued that soft paternalism increases the stability of given social norms, which in turn need not be efficient, nor in the material self-interest of a majority of individuals. Soft paternalism is argued to be an essentially conservative concept of policy-making in the sense that it tends to increase the longevity of status quo social norms.